Use of hair colouring products and risk of multiple myeloma among US women. Issue 1 (19th September 2008) - Koutros, S; Baris, D; Bell, E; Zheng, T; Zhang, Y; Holford, T R; Leaderer, B P; Landgren, O; Hoar Zahm, S
Abstract : Objective: To evaluate the association between personal hair dye use and risk of multiple myeloma among women. Methods: A population-based case–control study of 175 cases of multiple myeloma and 679 controls. Cases and controls were interviewed regarding the type and colour of hair colouring product used, age at first use, age use stopped, duration, and the frequency of use per year. Odds ratios (ORs) and 95% confidence intervals (CI) were estimated using unconditional logistic regression to compare never users with four exposure groups: all users, ever semi-permanent dye users, ever permanent dye users and dark permanent dye users (most frequent use). Results: No association was found between ever reporting hair colouring product use and myeloma risk among all users (OR 0.8; 95% CI 0.5 to 1.1), semi-permanent dye users (OR 0.7; 95% CI 0.4 to 1.2), permanent dye users (OR 0.8; 95% CI 0.5 to 1.1) or dark permanent dye users (OR 0.8; 95% CI 0.5 to 1.3). There were no significant associations among women who used hair dyes before 30 years of age, started use before 1980, had ⩾240 lifetime applications, or had used dark permanent dye for 28 or more years. Conclusion: No evidence of an association between hair colouring product use and myeloma risk was found. However, given the conflicting body of literature on hair colouring product use and risk of multiple myeloma, this question should be further evaluated in larger studies or consortia, and in high risk groups.